Uji Efektivitas Pemberian Fermentasi Air Kelapa (Cocos nucifera L.) Terhadap Pertumbuhan Tanaman Caisim (Brassica juncea L.) Varietas Tosakan - Cindy Maria Margaretheresia Simanjuntak; Ani Lestari; Hayatul Rahmi (Peneliti.net, 2021)
The mustard plant (Brassica juncea L.) is one of the vegetable commodities which very potential to be developing, because this comodities high economic value. The aims of this experiment was to fine out the concentration of coconut water fermentation that is most suitable for the growth and yield of mustard. This research has been conducted at Teluk Jambe Timur, Karawang district, West Java in March to April 2021. This research used experimental method with randomized block design (RBD) consisting of 6 treatments in 4 replication. The treatments were , treatment (NPK), treatment B (25 %), treatment C (50 %), treatment D (75 %) and treatment E (100 %). The data of research are analyzed by the analysis of variance at 5 % significance level and if the real effect is done by further test with DMRT test at 5 % significance level. The results showed that the treatment of concentration of water coconut fermentation had no effect on plant height age 14 day after planting (DAP), the number of leaves age 21 DAP, and significant effect on plant height age 7, 21, and 28 DAP, the number of leaves age 7, 14, and 28 DAP. The best treatment of coconut water fermentation was found on treatment C and D.